Use of an electrical stimulation-induced fatigue protocol to evaluate the myotropic effects of metabolic-active agents in db/db mice - V. A. Prikhodko; T. M. Matuzok; A. Yu. Grishina; V. E. Kovanskov; Yu. I. Sysoev; M. V. Titova; E. V. Popova; A. M. Nosov; D. Yu. Ivkin; S. V. Okovityi (Разработка и регистрация лекарственных средств, 2025)
Introduction. Type 2 diabetes mellitus (T2DM) is a chronic condition characterized by insulin resistance, impaired glucose tolerance, and hyperglycaemia. T2DM is a proven risk factor for peripheral neuropathies as well as muscle contractility and function impairments. The biguanide metformine, experimental compound maloben, and preparations of various Panax species have a considerable potential for the treatment of T2DM and its skeletal muscle complications. As a test to evaluate muscle contractility and the effectiveness of its recovery, Gregory et al. have developed a protocol of electrical stimulation-induced fatigue (ESIF) which includes measuring grip strength after fatiguing the biceps brachii muscle with high-frequency electrical stimulation using implantable electrodes.Aim. In this work, we attempted to assess the applicability of a modification of said protocol in order to evaluate the myotropic effects of metformin, maloben, and extracts from suspension cell cultures of Panax ginseng C.A. Mey. (PGE), P. vietnamensis Ha & Grushv. (PVE), and P. japonicus (T. Nees) C.A. Mey. (PJE) in the leptin-resistant db/db mice, one of the most popular modern T2DM models.Materials and methods. The experiments were carried out in 60 young adult (2 months old) male C57Bl/Ks-db+/+m (db/db) mice weighing 45–50 g, randomized into 6 groups: 1) Control (n = 10; 0.9 % saline); 2) PGE (n = 10; 50 mg/kg); 3) PVE (n = 10; 50 mg/kg); 4) PJE (n = 10; 50 mg/kg); 5) maloben (n = 10; 60 mg/kg); 6) metformin (n = 10; 300 mg/kg). All drugs were administered via oral gavage using a feeding tube once daily for 2 months. Following the treatment period, forelimb and all-four limb grip strength (g) was assessed using the Grip Strength Meter (TSE Systems, Germany). Using stimulation electroneuromyography, we measured the compound muscle action potential (CMAP) amplitudes in the gastrocnemius induced by single-stimulus sciatic nerve stimulation, and assessed the dynamics of CMAP amplitudes during the first 5 min following the ESIF protocol completion.Results and discussion. Following treatment period completion, no significant changes were observed between the groups in grip strength or gastrocnemius CMAP amplitude under single-stimulus stimulation. Controlled ESIF of the muscle caused a 18.83–35.23 % (relative to baseline) decrease in CMAP amplitudes (p < 0.01 for all groups) that was significantly smaller in the PVE, PJE, and maloben groups vs. control (p < 0.05). The post-ESIF recovery period was associated with a 10.18–14.79 % increase in CMAP amplitudes that was significant in all groups except PGE (p < 0.01 for control, PVE, and PJE; p < 0.05 for maloben and metformin). No significant differences from control were observed in any of the treatment groups regarding net recovery.Сonclusion. The proposed protocol represents a functional test suitable to assess the recovery effectiveness of electrical activity of a skeletal muscle following its controlled fatigue. Using the described protocol, we were able to detect beneficial effects of PVE, PJE, and maloben (but not PGE or metformin) on the recovery of gastrocnemius contractility following tetanization in diabetic db/db mice. The ESIF test is sensitive to the myotropic effects of metabolic agents, minimally invasive, and acceptable under chronic experiment conditions.